UJI PERTUMBUHAN FUSARIUM SP PEMBENTUK GUBAL GAHARU (AQUILARIA MALACCENSIS) PADA VARIASI MEDIA TUMBUH DAN SUHU - Mirani, Eva Dwi; Burhanuddin, .; Suryantini, Rosa (JURNAL HUTAN LESTARI, 2016)
Agarwood is non timber products of Aquilaria malaccensis that have a high economic value, so it can developed to  improve the Indonesian public income. Agarwood formed as a respond of Fusarium sp infection. The success of  Fusarium sp infection in A. malaccensis influenced by medium and temperature of Fusarium sp growth. The growth of Fusarium sp is determined by the medium growth. Therefore, the study aimed was to obtain the optimal medium and temperature for the fungal growth. This research done to isolation Fusarium sp at PDA medium, rice extract and agarwood A. malaccensis extract. The treatment consisted were a medium type (PDA, rice extract, agarwood  A. malaccensis extract) and used temperature varition (5 oC, 29 oC, 35 oC), designed randomized complete factorial and the treatment was repeated three times. The results of this study indicated that agarwood A. malaccensis extract at temperature of 29 °C and 35 °C could increase better than rice extract. However at 35 o C PDA medium more increase formed than agarwood A. malaccensis extract. It can be concluded the growth effective if inoculation Fusarium sp done at temperature 29 oC – 35 oC with inoculums such as PDA dan agarwood A. malaccensis extract. Keywords : A. Malaccensis, Fusarium sp, PDA, rice extract